2004
DOI: 10.1007/s10522-004-2473-3
|View full text |Cite
|
Sign up to set email alerts
|

Life course breast cancer risk factors and adult breast density (United Kingdom)

Abstract: Objective: To determine whether risk factors in childhood and early adulthood affect later mammographic breast density. Methods: Subjects were 628 women who attended a medical examination at the University of Glasgow Student Health Service , responded to a questionnaire (2001) and had a screening mammogram in Scotland (1989Scotland ( -2002. Mammograms (median age of 59 years) were classified using a six category classification (SCC) of breast density percent. Logistic regression was used to determine associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 38 publications
7
35
2
Order By: Relevance
“…The percentage of women in the 'most dense' Wolfe category was higher in this study than that reported in a study of similarly aged women in the United Kingdom [12]. Of the six other studies to investigate the potential association between birth weight and later mammographic density, two used the Wolfe categories [11,12]; two, on one cohort [13,15]; used a six-category classification that showed strong correlation with the Wolfe scale [13]; and two used computer-assisted measurements of density [14,16]. The only previous significant associations were seen in the latter two studies that used computer-assisted estimations of density [14,16], although one was limited to self-reported birth weight data [14], and the other had incomplete birth data due to its retrospective nature [16].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The percentage of women in the 'most dense' Wolfe category was higher in this study than that reported in a study of similarly aged women in the United Kingdom [12]. Of the six other studies to investigate the potential association between birth weight and later mammographic density, two used the Wolfe categories [11,12]; two, on one cohort [13,15]; used a six-category classification that showed strong correlation with the Wolfe scale [13]; and two used computer-assisted measurements of density [14,16]. The only previous significant associations were seen in the latter two studies that used computer-assisted estimations of density [14,16], although one was limited to self-reported birth weight data [14], and the other had incomplete birth data due to its retrospective nature [16].…”
Section: Discussioncontrasting
confidence: 61%
“…However, the limited research so far into the association between birth weight and mammographic density has reported inconsistent findings [11][12][13][14][15][16]. A number of other factors have been identified as risk factors for breast cancer, including exposure to oestrogen and other hormones [17], pregnancy-related factors, such as older age at first birth, higher parity, older age at last birth, short duration of breast feeding [18] early menarche [19], and levels of body fat, the risk relating to the latter varying with pre-and post-menopausal breast cancers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that smoking had a negative effect on mammographic density (Jeffreys et al, 2004;Bremnes et al, 2007;Butler et al, 2010), whereas others showed that cigarette smoking did not influence breast density (Gapstur et al, 2003;Ishihara et al, 2013;Dai et al, 2014). We failed to identify a significant association between smoking habits and mammographic density in premenopausal women; however, certain observations warrant cautious consideration because of the extremely low percentage of women in our study population who smoked.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have shown that breast density decreases with BMI and parity, whereas it increases with age at first birth, age at menopause, age at menarche, and family history of breast cancer [16][17][18][19]. Breast density also differs by race; black and Asian women generally have denser breasts than white women [20,21].…”
Section: Introductionmentioning
confidence: 99%